Assessment of teachers’ dedication, discipline, knowledge and skills in Kwara state basic schools, Nigeria - Kamaldeen Olohundare Sulyman (Journal of Education and Learning (EduLearn), 2020)
This study examined teachers’ dedication, discipline, knowledge and skills in Kwara State basic schools, Nigeria. The study population comprised all the 1,591 head teachers, 3,907 assistant head teachers; and 440 principals, 1,112 vice principals and all the students in Kwara State lower and upper basic schools respectively. Multi-stage sampling technique was used to arrive at 30 head teachers, 78 assistant head teachers, 30 principals and 71 vice principals; and 20 Basic Nine students from each of the sampled upper basic schools as respondents in the study. Questionnaire was used to collect data, while mean and standard deviation were used to analyse the data. The findings of the study revealed that teachers’ dedication in Kwara State basic, Nigeria was average ((X ) ̅ = 3.06). The study concluded that Kwara State basic school teachers should be more dedicated to their job by regularly preparing lesson notes, going to the classrooms at the right time and ensuring that the learners have a better understanding of the concepts taught.